2018
DOI: 10.1089/hum.2017.047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Zinc Finger Nucleases Versus CRISPR-Specific Nucleases for Genome Editing of the Wiskott-Aldrich Syndrome Locus

Abstract: Primary immunodeficiencies, including Wiskott-Aldrich syndrome (WAS), are a main target for genome-editing strategies using specific nucleases (SNs) because a small number of corrected hematopoietic stem cells could cure patients. In this work, we have designed various WAS gene-specific CRISPR/Cas9 systems and compared their efficiency and specificity with homodimeric and heterodimeric WAS-specific zinc finger nucleases (ZFNs), using K-562 cells as a cellular model and plasmid nucleofection or integration-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Unlike ZFN and TALEN that their target recognition is in demand of laborious protein design and synthesis for each target, CRISPR machinery is activated by guidance of a single RNA, sgRNA. Therefore, along with noticeable reduction in the time of design and construction, RNA leadership results in feasibility of CRISPR for multi-targeting, widespread genome manipulation or screening, and adoption in different biological contexts [ 49 , 50 ].…”
Section: Crispr the Treasure Trove Of Gene-editing Technologiesmentioning
confidence: 99%
“…Unlike ZFN and TALEN that their target recognition is in demand of laborious protein design and synthesis for each target, CRISPR machinery is activated by guidance of a single RNA, sgRNA. Therefore, along with noticeable reduction in the time of design and construction, RNA leadership results in feasibility of CRISPR for multi-targeting, widespread genome manipulation or screening, and adoption in different biological contexts [ 49 , 50 ].…”
Section: Crispr the Treasure Trove Of Gene-editing Technologiesmentioning
confidence: 99%
“…This is reflected in a number of recent publications. 65,[76][77][78] In addition the method described above can be generally applied for any engineered protein, and by optimizing the Ni(II)-induced protein hydrolysis to be significantly accelerated it may significantly contribute to this field. Most commonly occurring Zn(II) binding site donor set in ZF units.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed similar behavior of heterodimeric zinc finger proteins and CRISPR/Cas9 for homology-directed gene knock-in strategies (88% and 83%, respectively, of the donors inserted in the target locus), whereas homodimeric zinc finger proteins showed only 45% on-target insertions [45].…”
Section: Dna Targeting Strategiesmentioning
confidence: 91%